The potential therapeutic role of extracellular vesicles in critical-size bone defects: Spring of cell-free regenerative medicine is coming - Liu, Fen; Sun, Tianyu; An, Ying; Ming, Leiguo; Li, Yinghui; Zhou, Zhifei; Shang, Fengqing (Frontiers in Bioengineering and Biotechnology, 2023)
In recent years, the incidence of critical-size bone defects has increased significantly because of trauma, tumor and infection. Critical-size bone defects seriously affect the patients’ motor functions and quality of life, and increase the need for additional clinical treatments. Bone tissue engineering (BTE) has made great progress in repairing critical-size bone defects. As one of the main components of BTE, stem cell-based therapy is considered as a potential effective strategy to regenerate bone tissues. However, there has some disadvantages that restrict its wider clinical applications. Evidences have shown that positive biological effects of stem cells on tissue repairing are in large part through paracrine action by nano-structured extracellular vesicles (EVs), which could overcome the limitations of traditional stem cell-based treatments. Besides stem cells-derived EVs, the potential therapeutic roles of non stem cells-derived EVs in critical-size bone defects repair also attract attentions by scholars in recent years. Nowadays, development of EVs-mediated cell free regenerative medicine is still in the preliminary stage, and the specific mechanisms remain elusive. Herein, authors first reviewed the research progress and possible mechanisms of EVs combined with BTE scaffolds to promote bone regeneration via bioactive molecules. Engineering modified EVs are an emerging component of BTE. The main progresses and opportunities of them will be discussed then. Finally, future perspectives and challenges of the developing EVs-based regenerative medicine will be given. This review may provide a theoretical basis for the future development of the EVs-based biomedicine and provide clinical references for promoting the repair of critical-size bone defects.